The Effectiveness of the Joyful Mathematics Model Assisted by Magic Box Media on Early Childhood Understanding of Numbers and Numerals - Sarmi Sriyani; Syamsulrizal Syamsulrizal; Alman Alman (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study aims to analyze the effectiveness of the Joyful Mathematics Model assisted by Magic Box media in improving early childhood understanding of numbers and numerals. The problem underlying this study is the low numeracy ability of children due to learning practices that remain conventional and lack play-based activities and concrete learning media. This study employed a quantitative approach with a quasi-experimental design using a pretest-posttest control group design. The research subjects consisted of 13 children from Group B at TK Aisyiyah Bustanul Athfal 9 Salawati. Data were collected using a number and numeral understanding test instrument that had been tested for validity and reliability. The results showed a significant improvement in children’s numeracy ability, as indicated by an increase in the mean score from 71.92 in the pretest to 89.23 in the posttest. The paired sample t-test results showed a t-value of -8.285 with a significance value of p < 0.05, indicating a significant difference between the results before and after the treatment. In addition, the distribution of students’ ability categories also shifted from the “fair” and “good” categories to being predominantly in the “very good” category. The conclusion of this study is that the Joyful Mathematics Model assisted by Magic Box media is effective in improving early childhood understanding of numbers and numerals. This study provides practical contributions for early childhood education teachers in developing mathematics learning that is innovative, enjoyable, and based on concrete media, as well as implications for improving the quality of numeracy learning in early childhood education.